2019
DOI: 10.1038/s41467-019-09174-1
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase 1 accelerates vascular calcification by upregulating Runx2

Abstract: Vascular calcification is highly prevalent in end-stage renal diseases and is predictive of cardiovascular events and mortality. Poly(ADP-ribose) polymerase 1 (PARP1) inhibition or deletion is vasoprotective in several disease models. Here we show that PARP activity is increased in radial artery samples from patients with chronic renal failure, in arteries from uraemic rats, and in calcified vascular smooth muscle cells (VSMCs) in vitro. PARP1 deficiency blocks, whereas PARP1 overexpression exacerbates, the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 58 publications
0
86
0
Order By: Relevance
“…Yu et al [37] shed light on the interaction between TUG1 and miR-204-5p in calci c aortic valve disease (CAVD), and reveal that TUG1 actively regulates posttranscriptional expression of Runx2 by sponging miR-204-5p in CAVD. Similarly, Wang et al [38] identi ed that PARP1 promotes osteogenesis and calci cation of VSMCs by reducing translational inhibition of miR-204, thereby increasing Runx2 protein levels. Xiao et al [39] reported overexpression of miR-204 e ciently reversed the MALAT1-induced upregulation of Smad4 and then prevented osteogenic differentiation of human aortic valve interstitial cells (VICs).…”
Section: Mirna-204 May Play a Critical Role In Cardiovascular Diseasesmentioning
confidence: 97%
“…Yu et al [37] shed light on the interaction between TUG1 and miR-204-5p in calci c aortic valve disease (CAVD), and reveal that TUG1 actively regulates posttranscriptional expression of Runx2 by sponging miR-204-5p in CAVD. Similarly, Wang et al [38] identi ed that PARP1 promotes osteogenesis and calci cation of VSMCs by reducing translational inhibition of miR-204, thereby increasing Runx2 protein levels. Xiao et al [39] reported overexpression of miR-204 e ciently reversed the MALAT1-induced upregulation of Smad4 and then prevented osteogenic differentiation of human aortic valve interstitial cells (VICs).…”
Section: Mirna-204 May Play a Critical Role In Cardiovascular Diseasesmentioning
confidence: 97%
“…It has been shown that miR-204 promotes adipogenesis while it suppresses osteogenesis through direct inhibition of RUNX2 translation in MSCs and bone marrow stem cells [85]. A similar scenario was observed in VSMCs; Cui et al showed that down-regulating miR-204 contributed to the development of VC in murine cells and calcified aortas through RUNX2 suppression [15], while Wang et al further validated this relationship in human samples [50]. Lin and colleagues additionally showed that miR-204 could also oppose the progression of VC by targeting DNA methyltransferase 3a (DNMT3a) and altering DNA methylation status [41].…”
Section: Negative Vc-regulating Mirnasmentioning
confidence: 82%
“…Among them, 15 (40.5%) have been confirmed or are suspected to promote or aggravate VC in different scenarios, while 22 (59.5%) protect against VC formation or progression. Direct gene targets have been identified for 14 miRNAs with negative VC regulatory capacity, including miR-29a/29b [14], miR-29b-3p [34], miR-30b [16,47], miR-30c [16], miR-30e [25], miR-34b/34c [29,64], miR-125b [13,22] miR-133a [19], miR-135a [30], miR-182 [42], miR-204 [15,41,50], and miR-205 [21], while few direct targets have been identified for miRNAs with VC enhancement ability (miR-34a [39], miR-128-3p [48], and miR-135a-3p [17]). In the following sections, we describe the clinical features of each VC-regulating miRNA based on their propensity for positive or negative vascular influences.…”
Section: Mirnas In Vc: Positive and Negative Vc Regulatorsmentioning
confidence: 99%
“…and Chang Gung University College of Medicine, Kaohsiung, Taiwan. 2 Department of Food Science, National Chiayi University, Chiayi, Taiwan. 3 Graduate Institute of Clinical Medical Sciences, College of Medicine, Chang-Gung University, Taoyuan, Taiwan.…”
Section: Discussionmentioning
confidence: 99%